Resting heart rate as an index for monitoring physical condition during high altitude training in cross-country skiers - Takeda, M.; Kato, H.; Mimura, T.; Shimamoto, H.; Endoh, H.; Radak, Z. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Because of the fact that there are benefits and risks in high altitude training (Wilber, 2003), it is reasonable to have an index for monitoring physical condition and acclimatization status in high altitude training. In this study, we have evaluated physiological meanings of resting heart rate for monitoring the physical condition and acclimatization status during 2 weeks of high altitude training in cross-country skiers.